(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Despite its detrimental effects on health, chewing khat appears to be becoming more commonplace globally as a daily habit, particularly in the nations where it originated. As a result, it is very possible that khat users will take drugs while they chew the drug. That is high among them, increasing the likelihood of harmful khat-drug interactions. In these situations, it is critical to assess the impact of simultaneous khat and clinical medication delivery.Objective: As a preliminary study to evaluate the effect of khat (Catha edulis Forsk) chewing on serum Random Blood Sugar (RBG) level in Type 2 Diabetic Mellitus (T2DM) patients treated with metformin.Material and Method: Seventy-six male participants between the ages of 25 and 70 were included in the trial, 38 of them were already metformin-treated T2DM patients with a prior diagnosis. The remaining 38 people had no family history of diabetes, were healthy, and were not diabetic. Whether the individuals in the aforementioned two groups regularly chewed khat or not was used as a supplementary criterion for division. Using a drop of blood taken from each patient, a calibrated glucometer was used to take three readings of RBG levels.Results: The findings showed that healthy persons (non-khat chewers) had RBG levels at 4 hours after lunch that were significantly different from their corresponding values at 2 hours earlier. Using an independent sample t-test to compare the RBG levels of healthy khat chewers to healthy non-khat chewers, it was discovered that khat chewers had significantly higher RBG levels 3 and 4 hours after lunch (P = 0.042 and 0.000, respectively). RBG levels at 4 h after lunch (2 h after khat chewing) were significantly lower by -54.36 when compared to the level at 2 h after lunch of the same group of diabetic khat chewers taking metformin, whereas levels at 3 h after launch (1 h after khat chewing) were not statistically different.Conclusion: When khat was consumed, healthy volunteers' serum RBG levels went up, whereas diabetic patients receiving metformin saw no change in their RBG levels.